2022
DOI: 10.3390/ijms23115961
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Classification, Expression and Duplication Analysis of bZIP Family Genes in Juglans regia L.

Abstract: Basic leucine zipper (bZIP), a conserved transcription factor widely found in eukaryotes, has important regulatory roles in plant growth. To understand the information related to the bZIP gene family in walnut, 88 JrbZIP genes were identified at the genome-wide level and classified into 13 subfamilies (A, B, C, D, E, F, G, H, I, J, K, M, and S) using a bioinformatic approach. The number of exons in JrbZIPs ranged from 1 to 12, the number of amino acids in JrbZIP proteins ranged from 145 to 783, and the isoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…We also identified binding sites for many important transcription factors, NAC [ 42 ], ERF [ 43 ], bHLH (Basic/Helix-loop-Helix) [ 44 ], among other TFBSs associated with plant growth and development, these different TFBSs may provide valuable clues for studying how plants affect growth and development by regulating the spatiotemporal expression of Juglandaceae 14-3-3. The weak codon preference of Juglandaceae family GRF genes is influenced by a combination of natural selection pressure and base mutations, and translational selection plays a dominant role in codon usage against mutational pressure, which is largely consistent with our previous studies within the walnut bZIP family [ 45 ].…”
Section: Discussionsupporting
confidence: 89%
“…We also identified binding sites for many important transcription factors, NAC [ 42 ], ERF [ 43 ], bHLH (Basic/Helix-loop-Helix) [ 44 ], among other TFBSs associated with plant growth and development, these different TFBSs may provide valuable clues for studying how plants affect growth and development by regulating the spatiotemporal expression of Juglandaceae 14-3-3. The weak codon preference of Juglandaceae family GRF genes is influenced by a combination of natural selection pressure and base mutations, and translational selection plays a dominant role in codon usage against mutational pressure, which is largely consistent with our previous studies within the walnut bZIP family [ 45 ].…”
Section: Discussionsupporting
confidence: 89%
“…In angiosperms, most plant genomes contain more than 40 bZIP genes ( Baloglu et al., 2014 ; Liu and Chu, 2015 ). In this research we identified 45 LchibZIP genes, less than rose with 48 bZIP genes ( Li et al., 2022b ), Juglans regia L. has 88 bZIP genes ( Zhang et al., 2022 ), and Sedum plumbizincicola has 92 bZIP genes ( Lu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 89%
“…Deeper analysis showed that, 10 LchibZIPs were duplicated through segmental duplications, and only four gene pairs through tandem duplication, as demonstrated by synteny analysis of the LchibZIPs. Similarly, in Juglans regia L. bZIP genome, one pair of tandem repeats and 46 pairs of fragment repeats were identified ( Zhang et al., 2022 ). In the pear bZIP genome, 12 pairs of tandem repeats and 65 pairs of fragment repeats were identified ( Ma et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… 8 About 17 bZIPs in yeast, 27 in fruit flies, 31 in nematodes, and 56 in humans have been discovered, 9 whereas in plants, more bZIPs were found, 127 in Arabidopsis thaliana , 216 in Zea mays , 210 in Nicotiana tabacum , 214 in Populus trichocarpa , 47 in Vitis vinifera , 70 in Solanum lycopersicum , 88 in Juglans regia, 135 in Malus domestica , and 352 in Glycine max , etc., also have been reported. 10 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%